Reflections on the children house of congress and the non-profanable play - André Cechinel; Rafael Rodrigo Mueller (Universidade Federal de Santa Catarina, 2017)
This essay intends to discuss the Children House of Congress - a Brazilian educational project through which children, after selective process in schools, are invited to play a political role similar to that of deputies in the formulation of laws - as a program that, instead of listening to children's particular politics, strange and ungraspable, imposes an adult-centered and silencing intervention. For this purpose, the text is divided into two parts: first, it discusses the relationship between childhood, play, and profanity; after that, it addresses the link between schools and the Children House of Congress, as an example of how the educational process sometimes incorporates the demands of the adult world. In summary, if childhood usually challenges adult life from the point of view of difference, the aestheticization of politics, as practiced by the Children House of Congress, inserts children in a world at the same time predictable and apparently inevitable.